Comparison of two different PNN training approaches for satellite cloud data classification - Azimi-Sadjadi, Mahmood R., author; Tian, Bin, author; IEEE, publisher (Colorado State University. Libraries, 2001)
This paper presents a training algorithm for probabilistic neural networks (PNNs) using the minimum classification error (MCE) criterion. A comparison is made between the MCE training scheme and the widely used maximum likelihood (ML) learning on a cloud classification problem using satellite imagery data.
Keywords: probabilistic neural network; minimum classification error; maximum likelihood; cloud classification